2015
DOI: 10.1039/c5dt02073e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a polyborosilazane/Cp2ZrCl2 hybrid precursor for the Si–B–C–N–Zr multinary ceramic

Abstract: A novel zirconium-contained polyborosilazane (PBSZ-Zr) was synthesized by chemical modification of a liquid polyborosilazane (LPBSZ) with Cp2ZrCl2. A Si-B-C-N-Zr multinary ceramic was prepared via pyrolysis of PBSZ-Zr. The properties and the ceramization process of PBSZ-Zr, as well as the microstructural development and properties of the derived SiBCN-Zr ceramic, were well studied. The active Si-H and N-H groups in LPBSZ react with Zr-Cl in Cp2ZrCl2 to form PBSZ-Zr polymers. The Zr content of the SiBCN-Zr cera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…13b, produced HfSiBCN ceramics that remained amorphous to 1300 °C before segregating during crystallisation [191], and which produced composites with carbon fibres with significantly better resistance to hydrothermal corrosion compared with silicon carbonitride [192]. Reaction of CpZrCl2 with a polyborosilazane polymer led to amorphous ZrSiBCN ceramics up to 1600 °C, where phase segregation during crystallisation was again observed [193].…”
Section: Incorporation Of Other Elementsmentioning
confidence: 99%
“…13b, produced HfSiBCN ceramics that remained amorphous to 1300 °C before segregating during crystallisation [191], and which produced composites with carbon fibres with significantly better resistance to hydrothermal corrosion compared with silicon carbonitride [192]. Reaction of CpZrCl2 with a polyborosilazane polymer led to amorphous ZrSiBCN ceramics up to 1600 °C, where phase segregation during crystallisation was again observed [193].…”
Section: Incorporation Of Other Elementsmentioning
confidence: 99%
“…The HfC–SiC composite ceramics are commonly synthesized by milling and sintering of HfC and SiC powder mixtures . However, due to the difficulties in dispersing of raw powders, it is hard to get products with uniform microstructure and distribution . Single‐source precursor synthesis approach has been applied to synthesize nanoscale composites in very recently .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, due to the difficulties in dispersing of raw powders, it is hard to get products with uniform microstructure and distribution. 9,11 Single-source precursor synthesis approach has been applied to synthesize nanoscale composites in very recently. 1,3,11,12 However, in several limited studies it is reported that the compositions of Hf-containing products are complicated, such as HfN x and HfC x N 1Àx , and exist in the obtained products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, polymer‐derived method has been extended to synthesize Si‐containing ceramic nanocomposites . In the last decade, ceramic nanocomposites have been shown to be excellent material candidates for applications in high‐temperature or harsh environments because their properties improve upon reduction in the size of the ceramic phases towards the nanoscale . For example, Kong's group has developed magnetic and high‐temperature‐resistant ceramic nanocomposites via the design of novel hyperbranched silicon and metal‐containing polymers .…”
Section: Introductionmentioning
confidence: 99%